Rapid Method for the Determination of 5-Hydroxymethylfurfural and Levulinic Acid Using a Double-Wavelength UV Spectroscopy - Junhua Zhang; Junke Li; Yanjun Tang; Guoxin Xue (The Scientific World Journal)
This study reports on a rapid method for the determination of levulinic acid (LA) and 5-hydroxymethylfurfural (HMF) in acid hydrolyze system of glucose based on UV spectroscopy. It was found that HMF and LA have a maximum absorption at the wavelengths of 284 nm and 266 nm, respectively, in a water medium, and the absorptions of HMF and LA at 284 nm and 266 nm follow Beer’s law very well. However, it was found that a major spectral interference species will arise in the quantification of HMF and LA; nonetheless, this interference can be eliminated through the absorption treatment of charcoal. Therefore, both HMF and LA can be quantified with a double-wavelength technique. The repeatability of the method had a relative standard deviation of less than 4.47% for HMF and 2.25% for LA; the limit of quantification (LOQ) was 0.017 mmol/L for HMF and 4.68 mmol/L for LA, and the recovery ranged from 88% to 116% for HMF and from 94% to 105% for LA. The present method is simple, rapid, and accurate. It is suitable to use in the research of the preparation of HMF and LA in biorefinery area.